Achieving superior performance for oxygen electrode catalyst by the assistance of NaCl to construct cobalt sulfide on nitrogen and sulfur dual-doped graphene. (19th July 2018) - Ma, Xiu-Xiu; He, Xing-Quan
Abstract: Developing highly active catalysts to promote oxygen reduction reaction and oxygen evolution reaction is of utmost importance. Herein, the Co4 S3 /NSG-NaCl catalyst is prepared via a NaCl-guided hydrothermal method. Control experiments by replacing NaCl with KCl, KBr, NaNO3, CaCl2 and NaBr reveal that NaCl promotes a more efficient oxygen electrode catalysis results due to its high affinity and high ionicity. By varying the amount of the raw materials, optimized compositions are contained in the catalyst. Physical characterization indicates the optimized catalyst is of high specific BET surface area (∼181 m 2  g −1 ) and porous structure, which enable to expose more active sites, and facilitate more rapid mass transfer at the interface of gas-liquid-solid. XPS measurements suggest the formation of pyridinic N, graphitic N, CoN and CoS active species. Stemming from the synergistic effects between Co4 S3 and nitrogen and sulfur dual-doped graphene, the optimized Co4 S3 /NSG-NaCl hybrid show excellent catalytic activity and stability for both oxygen reduction reaction and oxygen evolution reaction under corrosive media. Graphical abstract: An advanced Co4 S3 /NSG-NaCl catalyst for both ORR and OER was synthesized via a NaCl-guided hydrothermal method. Image 1 Highlights: NaCl-guided Co4 S3 /NSG composite is synthesized via an in-situ hydrothermal method. Co4 S3 /NSG-NaCl is of porous structure with a high BET surface area. Co4 S3 /NSG-NaCl exhibits high electrochemical activity and stability for both ORR and OER. The high electrochemical performance is due to the synergistic effects among components.